Pore size directs bone marrow stromal cell fate and tissue regeneration in nanofibrous macroporous scaffolds by mediating vascularization. (December 2018) - Gupte, Melanie J.; Swanson, W. Benton; Hu, Jiang; Jin, Xiaobing; Ma, Haiyun; Zhang, Zhanpeng; Liu, Zhongning; Feng, Kai; Feng, Ganjun; Xiao, Guiyong; Hatch, Nan; Mishina, Yuji; et al.
Graphical abstract: Abstract: In the U.S., 30% of adults suffer joint pain, most commonly in the knee, which severely limits mobility and is often attributed to injury of cartilage and underlying bone in the joint. Current treatment methods such as microfracture result in less resilient fibrocartilage with eventual failure; autografting can cause donor site morbidity and poor integration. To overcome drawbacks in treatment, tissue engineers can design cell-instructive biomimetic scaffolds using biocompatible materials as alternate therapies for osteochondral defects. Nanofibrous poly (l -lactic acid) (PLLA) scaffolds of uniform, spherical, interconnected and well-defined pore sizes that are fabricated using a thermally-induced phase separation and sugar porogen template method create an extracellular matrix-like environment which facilitates cell adhesion and proliferation. Herein we report that chondrogenesis and endochondral ossification of rabbit and human bone marrow stromal cells (BMSCs) can be controlled by scaffold pore architecture, particularly pore size. Small-pore scaffolds support enhanced chondrogenic differentiation in vitro and cartilage formation in vivo compared to large-pore scaffolds. Endochondral ossification is prevented in scaffolds with very small pore sizes; pore interconnectivity is critical to promote capillary ingrowth for mature bone formation. These results provide a novel strategy to control tissue regenerative processes by tunable architecture of macroporous nanofibrous scaffolds. Statement of significance: Progress in understanding the relationship between cell fate and architectural features of tissue engineering scaffolds is critical for engineering physiologically functional tissues. Sugar porogen template scaffolds have uniform, spherical, highly interconnected macropores. Tunable pore-size guides the fate of bone marrow stromal cells (BMSCs) towards chondrogenesis and endochondral ossification, and is a critical design parameter to mediate neotissue vascularization. Preventing vascularization favors a chondrogenic cell fate while allowing vascularization results in endochondral ossification and mineralized bone formation. These results provide a novel strategy to control tissue regenerative processes by tunable architecture of macroporous nanofibrous scaffolds.